2018
DOI: 10.1111/adb.12618
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study in Finnish twins highlights the connection between nicotine addiction and neurotrophin signaling pathway

Abstract: The heritability of nicotine dependence based on family studies is substantial. Nevertheless, knowledge of the underlying genetic architecture remains meager. Our aim was to identify novel genetic variants responsible for interindividual differences in smoking behavior. We performed a genome-wide association study on 1715 ever smokers ascertained from the population-based Finnish Twin Cohort enriched for heavy smoking. Data imputation used the 1000 Genomes Phase I reference panel together with a whole genome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…These genes tended to be involved in broad nervous system functions, such as: synaptic plasticity ( Cyfip2, Ret, Tubb3, Sptbn1, Sptbn2, Spatn2 ), glutamate transmission ( Slc1a2, Grin1, Glul ) and calcium signaling ( Calm1, Calm2, Calm3, Atp1b1, Camkv ) potentially indicating a conserved and pleotropic role for more general dimensions of drug use and/or addiction. Accordingly, previous research demonstrates genome‐wide associations of these genes with other human substance use disorder traits commonly co‐morbid with cocaine abuse/dependence, including: alcohol ( Arhgap21 35 ), tobacco ( Kif1a 36 ), cannabis ( Ret 37 ) and heroin ( Myh10 38 ) dependence symptoms, as well as internalizing ( Psd 39 , Tubb3 40 and Zwint 41 ) and externalizing psychiatric disorders ( Dnm1 42 and Fbxl16 43 ).…”
Section: Discussionmentioning
confidence: 97%
“…These genes tended to be involved in broad nervous system functions, such as: synaptic plasticity ( Cyfip2, Ret, Tubb3, Sptbn1, Sptbn2, Spatn2 ), glutamate transmission ( Slc1a2, Grin1, Glul ) and calcium signaling ( Calm1, Calm2, Calm3, Atp1b1, Camkv ) potentially indicating a conserved and pleotropic role for more general dimensions of drug use and/or addiction. Accordingly, previous research demonstrates genome‐wide associations of these genes with other human substance use disorder traits commonly co‐morbid with cocaine abuse/dependence, including: alcohol ( Arhgap21 35 ), tobacco ( Kif1a 36 ), cannabis ( Ret 37 ) and heroin ( Myh10 38 ) dependence symptoms, as well as internalizing ( Psd 39 , Tubb3 40 and Zwint 41 ) and externalizing psychiatric disorders ( Dnm1 42 and Fbxl16 43 ).…”
Section: Discussionmentioning
confidence: 97%
“…CLEC19A is a member of the C-type lectin superfamily identi ed in brain tissues based on the HPA RNA seq project. A literature search revealed few studies which reported the CLEC19A but researchers have not treated the role of the CLEC19A gene and its protein in much detail [51]. Our bioinformatic results have shown that the CLEC19A protein possesses a signal peptide and no transmembrane domain, which suggests that CLEC19A is a potential secreted protein.…”
Section: Discussionmentioning
confidence: 76%
“…This is similar to our previous combined WES-neuroimaging study, in which one SNP in CDH23 had a genotype effect on cortical thickness but no genotype-by-diagnosis interaction effect [ 32 ]. Notably, a previous WES study suggested that the variable number tandem repeat (VNTR) region of MUC6 is associated with late-onset Alzheimer’s disease [ 73 ], and a GWAS of Finnish twins found that a missense variant in MUC6 is associated with nicotine addiction [ 74 ]. Additionally, MUC6 has been reported to be associated with the neurotrophin signaling pathway through NFκB1 [ 74 , 75 ], and this may be a possible neurobiological pathway between MUC6 rs771995197 and alterations of the white matter integrity.…”
Section: Discussionmentioning
confidence: 99%